Mapping genomic regions for reproductive traits in beef cattle: Inclusion of the X chromosome - Diaz, Iara Del Pilar Solar; de Camargo, Gregório Miguel Ferreira; Cruz, Valdecy Aparecida Rocha da; Hermisdorff, Isis da Costa; Carvalho, Caio Victor Damasceno; de Albuquerque, Lucia Galvão [UNESP]; Costa, Raphael Bermal (Wiley, 2020)
Although the second largest chromosome of the genome, the X chromosome is usually excluded from genome-wide association studies (GWAS). Considering the presence and importance of genes on this chromosome that are involved in reproduction, the aim of this study was to evaluate the effect of its inclusion in GWAS on reproductive traits (scrotal circumference [SC], early pregnancy [P16] and age at first calving [AFC]) in a Nelore herd. Genotype data from 3,263 animals with the above-mentioned phenotypes were used. The results showed an increase in the variances explained by the autosomal markers for all traits when the X chromosome was not included. For SC, there was an increase of more than 10% for the windows on chromosomes 2 and 6. For P16, the effect was increased by almost 20% for windows on chromosome 5. The same pattern was found for AFC, with an increase of more than 10% for the most important windows. The results indicate that the noninclusion of the X chromosome can overestimate the effects of autosomes on SC, P16 and AFC not only because of the additive effect of the X chromosome itself but also because of its epistatic effect on autosomal genes.
Keywords: age at first calving; genome-wide association; Nelore; non-Mendelian inheritance; scrotal circumference prediction; single nucleotide polymorphism